Penerapan Simple Moving Average Dalam Sistem Penjualan Barang Berbasis Web Menggunakan Metode Extreme Programming - Badiwibowo Atim, Sandi (Jurnal Media Borneo, 2023)
ABC store is one that utilizes technology in terms of selling goods, the problems experienced in determining the sales price of goods still have to be manual when there is a change in the price of goods that occurs when there is data on the receipt of goods from suppliers. The purpose of this study is to apply the simple moving average method in determining the cost of goods sold so that the ABC Store does not have to recalculate the sales price when there is a change in the price of goods received from suppliers. By applying the simple moving average method, the store will find it easier to calculate the sales price because it has been done automatically using the system created. User Acceptance Test (UAT) testing is a trial stage carried out by end users to ensure that the system or software has met the predetermined functional and non-functional requirements, the results of processing data responses to user acceptance test respondents obtained a total score of 95.31%.